Comparison of knowledge, attitude, practice and predictors of self-medication with antibiotics among medical and non-medical students in Tanzania - Shitindi, Lusajo; Issa, Omary; Poyongo, Baraka P.; Horumpende, Pius Gerald; Kagashe, Godeliver A.; Sangeda, Raphael Z. (Frontiers in Pharmacology, 2024)
Self-medication with antibiotics (SMA) is a widespread problem in developing nations, including Tanzania. This study compared knowledge, attitudes, practices, and factors influencing antibiotic SMA among medical and non-medical students. The prevalence of SMA among medical students was 49.1 % and 59.2% among non-medical students, respectively. The mean knowledge score of medical students (6.4) was significantly higher (P-value <0.001) than that of non-medical students (5.6). The main factors influencing SMA practices were the availability of antibiotics without a prescription, easy access to pharmacies, and a lack of knowledge about the risks of SMA. This experience was pivotal in influencing medical students to take antibiotics, with a substantial proportion of 67.5% as opposed to 59.4% of non-medical students. Medical students were 1.6 times more likely to self-medicate with antibiotics than non-medical students (Adjusted Odds Ratio (AOR): 1.6; 95% Confidence Interval (CI): 1.2 -2.3, p-value=0.004). Age was also associated with selfmedication, with an AOR of 1.1 (95% CI: 1.04 -1.2, P-value =0.006) per year increase in age. Additionally, attitude was associated with self-medication, with an AOR of 1.05 (95% CI: 1.04-1.1, P-value =0.001) per unit increase in attitude score. No significant associations were found between sex, marital status, having children, year of study, knowledge score, and self-medication with antibiotics. This study emphasizes the importance of educational interventions and public awareness campaigns to promote antimicrobial stewardship, appropriate antibiotic use, and preventing pharmacies from dispensing antibiotics without a prescription.